2017
DOI: 10.1007/s00127-017-1439-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of migration on social capital and depression among older adults in China

Abstract: PurposeAn estimated 9 million elderly people accompanied their adult children to urban areas in China, raising concerns about their social capital and mental health following re-location. The aim of this study was to examine the effect of migration on social capital and depression among this population.MethodsMultistage stratified cluster sampling was applied to recruit the migrant and urban elderly in Hangzhou from May to August, 2013. Data were collected from face-to-face interviews by trained college studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 48 publications
(44 reference statements)
4
60
1
Order By: Relevance
“…We found that a higher level of social capital was associated with a lower likelihood of experiencing depressive disorders after adjustment for confounders in the total population, which is consistent with previous studies [6,10,11,27]. Li et al [10] and Han et al [6] showed that a lower level of social capital (concerning trust and reciprocity) was connected associated with suffering from depression among people in their later life. In line with a prior study [28], we also found social connection could reduce the risk of depression among older adults.…”
Section: Discussionsupporting
confidence: 91%
“…We found that a higher level of social capital was associated with a lower likelihood of experiencing depressive disorders after adjustment for confounders in the total population, which is consistent with previous studies [6,10,11,27]. Li et al [10] and Han et al [6] showed that a lower level of social capital (concerning trust and reciprocity) was connected associated with suffering from depression among people in their later life. In line with a prior study [28], we also found social connection could reduce the risk of depression among older adults.…”
Section: Discussionsupporting
confidence: 91%
“…The same as in China, the health of the elderly worsens with age, suffering from both cognitive and physical health issue (Smith et al,2014). In the case of China, the urban-rural dualistic structure has created a dual lifestyle and cultural belief (Li et al,2017). As older people move, they face drastic change on lifestyle and living environment, which have been reported by World Health Organization as main factors affecting health.…”
Section: Health and Health Care Utilization Of The Elderly In Chinamentioning
confidence: 99%
“…Moreover, the Migrant Parents need to acculturate to a new environment and leave a familiar culture behind (Mjelde and Lou,2006;Zhao,1999). The elders who used to live in villages lost their daily work, lifestyle and community networks when their change residence from rural to urban (Li et al,2017). This changing social environment has been linked to elder depression (Wu et al,2004;Dong et al,2012;Shen and Takeuchi,2001;Wang and Zhao,2012).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, urban environments provide more opportunities for various leisure activities, which may also contribute to the maintenance of cognitive function [10]. However, some empirical studies have also found that rural-to-urban elderly migrants adapted poorly to aspects of their daily lives [7] and were likely to lose their original social networks, which increased their risk of depression [11]. The association between migration and cognitive function change may show sex-related differences, as women tend to be more involved in family and social activities than men [12,13].…”
Section: Introductionmentioning
confidence: 99%